Mutual effect of extrinsic defects and electronic carbon traps of M-TiO2 (M = V, Co, Ni) nanorod arrays on photoexcited charge extraction of CdS for superior photoelectrochemical activity of hydrogen production - Mumtaz, A. (Elsevier Ltd, 2018)
Understanding the photoexcited charge carrier dynamics such as separation, transportation and extraction in smart hybrid nanocomposites is the key to high performance solar cells. Nanocomposites possess advantage of broader solar absorption with their fast photoexcited charge separation and transportation but their use as photocorrosion-stable material is yet to be explored. Also, bulk and surface defects in individual components of the nanocomposites boost the efficiency of the solar cells, despite of the fact the recombination of the photoexcited charges at the interfaces lead to a substantial loss of charges and realizing a big challenge. Herein, the extrinsic defects like bulk and surface defects are induced by transition metal (M = V, Co, Ni) doping of M â TiO2 nanorod arrays. Consequently, the hydrothermal synthesis method offers the tuning of the carbon trapping states depending upon the type of the metal doped in M â TiO2 that decelerates the charge carrier dynamics in the M-TiO2/CdS (M = V, Co, Ni) nanocomposites with the increase in the amount of carbon. Excellent charge extraction is observed in VâTiO2 (4 carbon) from its CdS sensitizer with photocurrent density of 2.06 mA/cm2 than NiâTiO2 (14.6 carbon), TiO2 (18.94 carbon) and CoâTiO2 (39.2 carbon) with photocurrent densities of 1.83, 1.46 and 1.34 mA/cm2 at 0 V versus Ag/AgCl under 100 mW/cm2 light intensity, respectively. This shows primary dependence of photoexcited charge dynamics upon the density of the carbon trapping states to be least while secondary dependence upon the density of the extrinsic defects in M â TiO2 to be maximum. This work creates a paradigm for future studies to have a broader insight of the photocatalyst's overall functioning to boost the efficiencies in solar cells by controlling the amount of electronic carbon traps during the synthesis of a large class of inorganic semiconductor photocatalysts. Â© 2018 Hydrogen Energy Publications LLC